SIMULATING MOLECULAR OPTICAL PROPERTIES OF POLYIMIDE FOR NONVOLATILE RESISTIVE PHOTOMEMORY DEVICES: Received: 07th July 2023 Revised: 31st October 2023, 06th November 2023, 8th November 2023 Accepted: 10th July 2023 - Wen-Luh Yang,; Pei-Ying Jiang,; Wei-Cheng Ou,; Pin-En Hsu,; Yi-Huan Pan,; Tang-Yi Liu,; I-Ming Tseng, (MATTER: International Journal of Science and Technology, 2024)
In this study, the focus was on utilizing the polyimide (PI) thin film as a resistive conversion layer for organic polyimide-based resistive random-access memory (ReRAM) applications. We utilized the 3D molecular editor WebMO to manipulate and analyze the structures of Aromatic-PI and Quinoid-PI molecules. The molecular chain length, molecular weight, and HOMO/LUMO molecular orbitals were investigated to gain insights into the fundamental properties of PI molecular structures. The analysis revealed that the Quinoid-PI molecule exhibited a shorter molecular chain compared to Aromatic-PI, attributed to the inability of the cyclic structure in Quinoid-PI to maintain a planar conjugated structure, resulting in an uneven overall structure and reduced molecular chain length (Norcorss, 1988). The research results demonstrate that the optical energy gap of Aromatic-PI remains constant regardless of the number of molecular bonds, with a value of approximately 3.2661 eV. In contrast, for Quinoid-PI, the optical energy gap undergoes a significant decrease as the number of molecular bonds ranges from 1 to 5. As the bond count increases to 20~23, the change in the optical energy gap gradually diminishes, ultimately resulting in an optical energy gap of 0.6932 eV. This observation indicates that longer molecular chains composed of Aromatic-PI act as insulators, while Quinoid-PI transforms into a low-energy gap conductor.